Synthesis of Cobalt Stearate as Oxidant Additive for Polystyrene Oxo-biodegradable - Asih Safitri, Endang
Polystyrene (PS) isolated from styrofoam waste has been modified by the addition of cobalt stearate (CoSt) as an oxidant additive for applications of PS oxo-biodegradable. Oxo-biodegradation process occurs in two stages, that are biotic and abiotic stage. At the stage of abiotic, PS undergo oxidative degradation due to the presence of CoSt as the oxidant additive and heating treatment, so that occurs the interruption of the main chain PS that generates shorter chain fragments that contain functional groups such as alcohols, aldehydes, ketones, and carboxylic. PS films with CoSt concentration of 0,075% and 0,2% (w/w) were heated at temperature of 50 ºC and 75 ºC for 10 days. Characteristics of the PS film before and after heating were analyze using FTIR spectroscopy (Fourier Transform Infrared), mechanical properties with tensile tester and thermal property with TGA (Thermogravimetric Analysis). PS film with the addition of 0,075% CoSt mass observed that increase in carbonyl index value, decrease in melting point, stress and strain after heating 75 ºC for 10 days. The effect of heating temperature of the film PS 0,2% CoSt was determined by carbonyl index value at heating temperature of 50 ºC and 75 ºC for 10 days. At the same concentration of CoSt, a higher heating temperature, PS film was faster degraded that was indicated by rapidly increasing index value of carbonyl in the FTIR results. At the stage of biotics, biodegradation test of PS films was carried out by activated sludge on solid media. Biodegradation test was conducted by measuring the weight loss of the polymer film after incubation for 5, 10, 20 and 30 days. The surface morphology of the polymer film was performed using SEM (Scanning Electron Microscopy). PS films with 0,075% CoSt without heating after incubation time for 30 days, the weight loss was about 1,69% while the film PS with 0,075% CoSt and followed with heating 75 ºC for 10 days, the weight loss was 16,17%.